2020
DOI: 10.17061/phrp3022009
|View full text |Cite
|
Sign up to set email alerts
|

Stemming the flow: how much can the Australian smartphone app help to control COVID-19?

Abstract: • We assessed the potential contribution of the COVIDSafe contact tracing app to the sustained control of COVID-19 following successful suppression of the pandemic in Australia during March-May 2020 • If a high level of community uptake can be achieved, the COVIDSafe app, combined with testing and social distancing, could have a valuable mitigating effect on a new wave of COVID-19 through enhanced and expedited case detection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
0
41
1
Order By: Relevance
“…Timely and effective contact tracing is an essential public health measure for curbing the transmission of COVID-19. Contact tracing apps are controversial in their design and level of effectiveness [ 3 , 5 , 6 ], but they might have the potential to prevent widespread community transmission and optimize the resources of overstretched public health organizations [ 9 ]. An important driver for their efficiency is widespread public adoption [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely and effective contact tracing is an essential public health measure for curbing the transmission of COVID-19. Contact tracing apps are controversial in their design and level of effectiveness [ 3 , 5 , 6 ], but they might have the potential to prevent widespread community transmission and optimize the resources of overstretched public health organizations [ 9 ]. An important driver for their efficiency is widespread public adoption [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contact tracing apps are controversial in their design and level of effectiveness [ 3 , 5 , 6 ], but they might have the potential to prevent widespread community transmission and optimize the resources of overstretched public health organizations [ 9 ]. An important driver for their efficiency is widespread public adoption [ 9 ]. Our study aimed to examine Australian participants’ understanding of the Australian Government’s COVIDSafe app and explore the reasons why some Australians chose not to download the app.…”
Section: Discussionmentioning
confidence: 99%
“…A number of countries have integrated this kind of tracing app into their deconfinement plans or are presently discussing this option [ 2 , 3 ]. Research has concentrated on contact tracing and symptom tracking systems [ 1 , 4 - 6 ] as well as the association between app usage and the epidemiological spread of the virus [ 7 ]. Some studies have focused on the differences between apps implemented in several countries [ 3 ], while others have analyzed the legal or ethical aspects (eg, data protection) [ 2 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In his parsing of the app’s effectiveness, Australian Deputy Chief Medical Officer, Dr Nick Coatsworth, suggested that because of movement restriction, people had not been circulating, so the ‘app hasn’t identified those cases’, and that as ‘numbers go up then the app can come into its own’ ( Coatsworth, 2020 ). With the groundswell for mask use in mind, Coatsworth (2020) cleverly sought to link the two, suggesting ‘if you are a supporter of mask use, you must also be based on the modelling, a supporter of downloading and activating the app’ (here he refers to the study by Sax Institute, see Currie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%